PREDICTING FACTORS FOR CHEMOTHERAPY-INDUCED PERIPHERAL NEUROPATHY IN COLORECTAL CANCER PATIENTS UNDERGOING CHEMOTHERAPY - Sabamnet, Sujintorn; Saneha, Chongjit; Poungkaew, Autchariya; Soparattanapaisan, Nopadol (JOURNAL OF THE POLICE NURSES AND HEALTH SCIENCE, 2022)
This correlational predictive study aimed to determine the predictive factors of chemotherapy-induced peripheral neuropathy (CIPN) in patients with colorectal cancer (CRC) undergoing chemotherapy. One hundred and two samples who met the inclusion criteria were recruited from two tertiary hospitals in Bangkok. Data collection tools included demographic questionnaires, namely EORTC QLQ-CIPN20, Stress test 5, and IPAQ and Health literacy. The reliability of EORTC QLQ-CIPN20, Stress test 5, and Health Literacy using Cronbach’s alpha coefficients were .86, .83, and .93, respectively. Only IPAQ was verified by Test-retest Reliability two weeks apart and its intra-class correlation coefficient (ICC) was equal to .85. The data were analyzed using descriptive statistics and logistic regression analysis by enter method. The results revealed that the samples were males (51.96%) with a mean age of 60.88 years (SD=10.47), and 90.20% of them had CIPN at a mild level (Mdn=7.40, IQR=9.72). The majority of the samples had mild stress (81.37%), moderate physical activity (55.88%), and high health literacy (81.37%). Age, stress, physical activity, and health literacy can jointly explain the variances of CIPN in patients with CRC undergoing chemotherapy at 41% (Negelkerke R2 =.41, p < .05). Only stress variables (OR=2.33, 95%CI=1.08 - 5.02, p= .031) and health literacy variables (OR=.95, 95%CI=.90 - 1.00, p=.041) were statistical predictors of CIPN. The findings of this study suggest that nurses and the health care team should assess stress, health literacy, and CIPN in order to decrease the risk of CIPN by reducing stress and promoting health literacy in patients with CRC undergoing chemotherapy.